Multiplexing - Mohammady, Somayeh (IntechOpen, 2019)
Mobile communication has been a critical part of everyday life for the last 30 years. As the demand for wireless communications and higher data rates on these links continues its rapid growth, engineers, scientists, and researchers are required to advance the hardware and software needed to deliver systems for 5G, Massive multiple-input, multiple-output (MIMO), and optical backhaul networks. Now, more than ever before, the fundamental concept of multiplexing is at play. This book is a unique reference for understanding the concept of multiplexing. It provides comprehensive coverage of the practical applications of multiplexing to help the reader better understand its use in these systems. It is a great resource, especially for engineers working on digital signal processing, radio frequency (RF), antenna design, beamforming, and network designs. The book contains chapters on the following topics: • History of multiplexing and how it applies to current technologies; • Different types and applications of multiplexing; • Multiplexing techniques in wireless networks; • Multiple-Input, Multiple-Output Orthogonal Frequency-Division Multiplexing (MIMO-OFD); • Direct-Sequence Optical-Code Division Multiple-Access (DS-OCDMA); • Optically multiplexed systems